Analysis on the equity differential on household healthcare financing in developing countries: Empirical evidence from Tanzania, East Africa - Felician Andrew Kitole; Robert Michael Lihawa; Eliaza Mkuna (Health Economics Review, 2022)
Background: Achieving equity in healthcare services has been a global priority. According to the literature, a slew of initiatives aimed at increasing household equity in healthcare fnancing have exacerbated the problem, making it hard for most developing countries to understand the real cause of the problem. Method: The non-experimental research design has been used to explore the Tanzania Panel Survey (NPS) data 2019/2020, to investigate equity diferential in household healthcare fnancing in Tanzania by the use of conventional instrumental variable methods of Two-stage and Three-stage least square methods Results: Despite the global agenda of universal health coverage, this paper reveals that 86 percent of Tanzania lacks health insurance with a high degree of inequitable distribution of health facilities as 71.54 percent of the population is in rural areas, yet these areas have poor health systems compared to urban ones. These disparities increase pressure on household healthcare fnancing and widen the inequity and equality gaps simultaneously. Additionally, a household's income, education, health care waivers, out-of-pocket expenditure, and user fees have been found to have a signifcant impact on household equity in healthcare fnancing. Conclusion: To reverse the situation and increase equity in household healthcare fnancing in most developing countries, this paper suggests that an adequate pooling system should be used to allow more people to be covered by medical prepayment programs, and the donor-funded programs in developing countries should focus on health sector infrastructure development and not the capacity building.
Keywords: 330; Health Financing; Health Equity; Instrumental Variable; Health Economics; Tanzania; Developing Countries